PEMBELAJARAN MENULIS NASKAH DRAMA DENGAN PENDEKATAN KONTEKSTUAL TEKNIK LEARNING COMMUNITY PADA SISWA KELAS XI MA TANWIRIYAH KALISARI BAURENO TAHUN PELAJARAN 2015/2016 - Muh. Ariful Burhan (PENTAS : Pendidikan Bahasa dan Sastra Indonesia, 2017)
absence of a follow-up to apply. This will make only limited students to understand it without any desire to apply the knowledge they have acquired. Students became bored and did not obtain the maximum results. Based on the above background, the researcher tried to use an alternative method is the application of contextual approach with community learning techniques with the aim to describe (1) lesson planning; (2) the implementation of learning; (3) assessment of learning; (4) the response of students in learning writing a drama with contextual approach with community learning techniques in class XI MA Tanwiriyah Kalisari Baureno in the Academic Year of 2015/2016. The method used in this study was a descriptive qualitative research method. Based on the survey results revealed that the description of the application of contextual approach to community learning techniques on the learning writing a drama in terms of: (1) planning of learning has been categorized well, this is evidenced in the learning process that is effective and has achieved the purpose of research; (2) the implementation of learning visits from student activity categorized well with the percentage of 78.33%; (3) assessment of student learning are in a good level with the classical learning completeness 90.71%; and (4) the response of students that are in the category of a very good result with the response of the classical percentage 90.30%.